Neurocognitive Dysfunction and Smaller Brain Volumes in Adolescents and Adults With a Fontan Circulation. Issue 9 (24th November 2020) - Verrall, Charlotte E.; Yang, Joseph Y.M.; Chen, Jian; Schembri, Adrian; d'Udekem, Yves; Zannino, Diana; Kasparian, Nadine A.; du Plessis, Karin; Grieve, Stuart M.; Welton, Thomas; Barton, Belinda; Gentles, Thomas L.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Neurocognitive outcomes beyond childhood in people with a Fontan circulation are not well defined. This study aimed to investigate neurocognitive functioning in adolescents and adults with a Fontan circulation and associations with structural brain injury, brain volumetry, and postnatal clinical factors. Methods: In a binational study, participants with a Fontan circulation without a preexisting major neurological disability were prospectively recruited from the Australia and New Zealand Fontan Registry. Neurocognitive function was assessed by using Cogstate software in 107 participants with a Fontan circulation and compared with control groups with transposition of the great arteries (n=50) and a normal circulation (n=41). Brain MRI with volumetric analysis was performed in the participants with a Fontan circulation and compared with healthy control data from the ABIDE I and II (Autism Brain Imaging Data Exchange) and PING (Pediatric Imaging, Neurocognition, and Genetics) data repositories. Clinical data were retrospectively collected. Results: Of the participants with a Fontan circulation who had a neurocognitive assessment, 55% were male and the mean age was 22.6 years (SD 7.8). Participants with a Fontan circulation performed worse in several areas of neurocognitive function compared with those with transposition of the great arteries and healthy controls ( P <0.05). Clinical factors associated with worse neurocognitive outcomes included more inpatient days during childhood, younger age at Fontan surgery, and longer time since Fontan procedure ( P <0.05). Adults with a Fontan circulation had more marked neurocognitive dysfunction than adolescents with a Fontan circulation in 2 domains (psychomotor function, P =0.01 and working memory, P =0.02). Structural brain injury was present in the entire Fontan cohort; the presence of white matter injury was associated with worse paired associate learning ( P <0.001), but neither the presence nor severity of infarct, subcortical gray matter injury, and microhemorrhage was associated with neurocognitive outcomes. Compared with healthy controls, people with a Fontan circulation had smaller global brain volumes ( P <0.001 in all regions) and smaller regional brain volumes in most cerebral cortical regions ( P <0.05). Smaller global brain volumes were associated with worse neurocognitive functioning in several domains ( P <0.05). A significant positive association was also identified between global brain volumes and resting oxygen saturations ( P ≤0.04). Conclusions: Neurocognitive impairment is common in adolescents and adults with a Fontan circulation and is associated with smaller gray and white matter brain volume. Understanding modifiable factors that contribute to brain injury to optimize neurocognitive function is paramount.